New Product Development Method Trends and Future Research : A Systematic Literature Review - Khannan, Muhammad Shodiq Abdul; Tontowi, Alva Edi; Herliansyah, Muhammad Kusumawan; Sudiarso, Andi (Institute of Research and Community Outreach - Petra Christian University, 2021)
Research on new product development (NPD) has led to tools, methods, models, and frameworks that enable researchers to develop better products. However, a comprehensive review of the methods, models and frameworks related to NPD is lacking. This literature study aims to identify research trends, methods, and frameworks used in NPD between 2010 and 2019. A systematic literature review is conducted by developing a structured research protocol. An analysis of 50 selected papers shows that research on NPD can be categorized into 15 conceptual papers, six review papers, 28 case studies, and one survey paper. This paper provides an overview of each tool and presents future research opportunities. This paper concludes that future research can be directed toward combining several methods to design products that satisfy consumer desires with shorter design times, aspects of NPD collaboration, and aspects of changing consumer preferences.